Work and worker health in the post-pandemic world: a public health perspective. (February 2022) - Peters, Susan E; Dennerlein, Jack T; Wagner, Gregory R; Sorensen, Glorian
Summary: The COVID-19 pandemic has highlighted the importance of work in shaping population health and wellbeing. This Viewpoint applies a multilevel systems framework to assist in understanding the diverse and complex interactions of forces affecting worker health and wellbeing, and how trending changes in employment and working conditions have been accelerated by the pandemic. Government agencies concerned with population health and wellbeing, and economic activity must expand their capacity to monitor, evaluate, and respond to these trends. In addition, integrated enterprise and workplace-based approaches that consider the interactions among these multidimensional drivers will build organisation and worker resilience to navigate the continual changes in work and worker safety, health, and wellbeing in a post-pandemic world.